Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm reading a proof and I'm struggling with basic calculus here. Given the equation, $F[x, F(y, z)] = F[F(x, y), z] $ set $u = F(x, y)$ and $v = F(y, z)$ so you have

$$F(x, v) = F(u, z)$$

Now differentiate with respect to $x$ and $y$ leads to the following

  1. $F_{x}(x,v) = F_{x}(u,z)F_{x}(x,y)$
  2. $F_{y}(x,v)F_{x}(y,z) = F_{x}(u,z)F_{y}(x,y)$

I think, according to the chain rule, the derivative of $F[x, F(y, z)]$ or $F[x, u]$ with respect to x should equal $F_{x}(u,z)F_{x}(x,y)$. So number 1 makes sense. But when you differentiate that with respect to $y$, I don't understand how you get 2.

share|improve this question

2 Answers 2

You seem to have a typo; I presume you meant $F(x,v)$ where it says $F[x,u]$?

You don't get 2. by differenitating 1. with respect to $y$, but by differentiating the original equation, $F(x,v)=F(u,z)$, with respect to $y$.

share|improve this answer

You are given that $$F(x,F(y,z)) = F(F(x,y),z)$$ Calling $F(x,y) = u$ and $F(y,z) = v$, we then have that $$F(x,v) = F(u,z)$$ Differentiating $F(x,v) = F(u,z)$ with respect to $x$, gives us $$\dfrac{\partial F(x,v)}{\partial x} + \dfrac{\partial F(x,v)}{\partial v} \underbrace{\dfrac{\partial v}{\partial x}}_{0} = \dfrac{\partial F(u,z)}{\partial u} \dfrac{\partial u}{\partial x} + \dfrac{\partial F(u,z)}{\partial z} \underbrace{\dfrac{\partial z}{\partial x}}_{0}$$ Hence, you get the first equation i.e. $$F_x(x,v) = F_u(u,z)u_x = F_u(u,z)F_x(x,y)$$ Differentiating $F(x,v) = F(u,z)$ with respect to $y$, gives us $$\underbrace{\dfrac{\partial F(x,v)}{\partial y}}_{0} + \dfrac{\partial F(x,v)}{\partial v} \dfrac{\partial v}{\partial y} = \dfrac{\partial F(u,z)}{\partial u} \dfrac{\partial u}{\partial y} + \dfrac{\partial F(u,z)}{\partial z} \underbrace{\dfrac{\partial z}{\partial y}}_{0}$$ Hence, you get the second equation i.e. $$F_v(x,v)v_y = F_u(u,z)u_y$$ $$F_v(x,v)F_y(y,z) = F_u(u,z)F_y(x,y)$$

share|improve this answer
    
thanks! In both equations, you used Fv and Fu instead of Fx and Fy. Why? Does it make a difference? –  user1507889 Oct 21 '12 at 21:16

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.